Facade, Marshall Sons and Co. building - Ghosh, Ayan (2023)
The imposing Marshall Sons and Co. is a corner building at the intersection of Shoorji Vallabhdas Road and Shahid Bhagat Singh Marg. The building was designed in Edwardian Baroque style by architect Charles Frederick Stevens, son of the late Frederick W Stevens who had been Mumbai's most celebrated architect during the Victorian Gothic phase.